The Länder and German federalism - Gunlicks, Arthur B., 1936- (Manchester ; New York : Manchester University Press ; New York : Distributed exclusively in the USA by Palgrave, 2003)
This book provides a detailed introduction to how the Länder (the sixteen states of Germany) function not only within the country itself but also within the wider context of European political affairs. Some knowledge of the role of the Länder is essential.
The origins of the Länder -- Theory and constitutional framework of German federalism -- Administrative structures in Germany -- The Land constitutes -- Financing the federal system -- The German Land parliaments (Landtage) -- The Land parliament deputies in Germany -- Parties and politics in the Länder -- Election in the Länder -- The Länder, the Bundesrat, and the legislative process in Germany and Europe -- European and foreign policy of the Länder -- The German model of federalism.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Federal government -- Germany; Germany -- Politics and government -- 1990-; Society and social sciences; Politics and government; Regional government; POLITICAL SCIENCE -- Civics & Citizenship; POLITICAL SCIENCE -- Terrorism; Federal government; Politics and government; Germany; Since 1990; Multi-User.